Desenvolvimento e caracterização de locos microssatélites a partir do genoma de Handroanthus impetiginosus (Mart. ex DC) Mattos - Ayasta, Betty Alessandra Del Milagro Rivera (2022)
The pink ipê (Handroanthus impetiginosus) is a native forest species of the Atlantic Forest with high economic potential due to the durability and density of its wood, as well as its high landscape value because of the beauty of its inflorescences. However, the species has been illegally exploited and has no management plan. The pink ipê (Handroanthus impetiginosus) does not have microsatellite markers developed yet, which limits the possibilities of genetic studies either in natural in eventual breeding populations. The objective of this work is to identify and characterize the microsatellite loci in the genome of H. impetiginosus, as well as to develop microsatellite markers for the species. The genome sequences of H. impetiginosus, available in the NCBI Bank, were analyzed in the MISA program, which locates and classifies the microsatellites according to the type and number of repetitions. In the pink ipê genome, 85,473 microsatellite regions were detected, of which 53% were mononucleotides, 36% dinucleotides, 5% trinucleotides, 1% tetranucleotides and 5% compounds. The most frequent dinucleotide motif type was AT/AT with 45% and of trinucleotides was AAT/ATT with 21%. Most microsatellites were in intergenic regions (86%), followed by introns (12%). Primers were designed for the 50 longest intergenic di- and tri-nucleotide loci. The primers were used in polymerase chain reactions (PCR) and the quality of amplifications was checked on agarose gel. The 20 loci with the best results had one of their primers marked with fluorophores (6-FAM, NED or JOE) for high-resolution genotyping via capillary electrophoresis. These 20 loci were evaluated in a screening with five samples of H. impetiginosus. The nine best polymorphic loci were selected for final genotyping in a sample of 20 individuals of H. impetiginosus. This genotyping obtained an average of 7.89 alleles per locus, observed heterozygosity of 0.72 and expected heterozygosity of 0.78. The transferability of these nine loci was also tested in nine samples of Handroanthus serratifolius and eight samples of Handroanthus ochraceus. Of these, seven amplified in H. serratifolius and four in H. ochraceus. The transferability of the loci was also evaluated in Tabebuia roseo-alba and T. aurea, but none of them amplified. Among the successfully genotyped species, 54, 41 and 17 private alleles were identified in H. impetiginosus, H. serratifolius and H. ochraceus, respectively. In general, the microsatellite markers developed in this work in H. impetiginosus allow the analysis of genetic diversity not only in this species but also in H. serratifolius and H. ochraceus.